PERFORATION AS A COMPLICATION OF THE DIAGNOSTIC UPPER AND LOWER ENDOSCOPY OF THE GASTROINTESTINAL TRACT - Ivailo P. Vazharov (Peytchinski Publishing, 2012)
Purpose: The purpose of this examination is to evaluate the risk of perforation during endoscopy of upper and lower gastrointestinal tract.Patients and methods used: 1210 diagnostic gastroduodenoscopies and 412 colonoscopies of hospitalized patients were performed by two experienced endoscopists for the period March 2007 - March 2012 at MHAT Varna, MMA. The endoscopies were performed without premedication and sedation. The patients were examined for complications of the procedure during and after the endoscopy. One of the most serious complications is the perforation of the oesophagus, stomach or the large intestine.Results: We had no perforations caused by the examination during the 1210 upper endoscopies performed. We had 2 perforations (0,48%) from the 412 colonoscopies performed, which were treated successfully surgically.Conclusions: The perforation is a rare but serious complication of the endoscopy of gastrointestinal tract, which can be healed completely.